A Retrospective Analysis of the Effects of Cardiac Rehabilitation on Health Markers and Performance Outcomes among Diabetic and Non-Diabetic Patients with Coronary Artery Bypass Grafting and Percutaneous Coronary Intervention - Amy N. McKeever; Phillip C. Drouet; Jesus A. Vera; William E. Thomas; Jared W. Coburn; Pablo B. Costa (MDPI AG, 2024)
Background: The aim of this study was to investigate the effects of cardiac rehabilitation on health markers and performance outcomes among diabetic and nondiabetic patients with coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI). Methods: One hundred and ninety-seven patients with PCI and CABG, who attended phase 2 cardiac rehabilitation, were included in the study. Patient data were separated by cardiac diagnosis, (PCI and CABG), diabetes category (diabetic and nondiabetic), number of sessions attended (12-24 or 25-36), and time (pre- to post-test). The Duke Activity Score Index and Patient Health Questionnaire-9 questionnaires and measurements for total cholesterol, high-density lipoprotein, low-density lipoprotein, triglycerides, and, if diabetic, A1c and fasting blood glucose, were taken at baseline and upon completion of the program. Results: High-density lipoprotein (p < 0.001), diastolic blood pressure (p = 0.004), Duke Activity Score Index questionnaire (p < 0.001), Patient Health Questionnaire-9 (p < 0.001), and A1c (p = 0.003) significantly improved from pre- to post-testing. Total cholesterol (p < 0.001) and low-density lipoprotein (p < 0.001) for the 25-36 nondiabetic PCI group significantly decreased. Triglycerides decreased for all 12-24 session groups (p = 0.015). Fasting blood glucose significantly decreased (p = 0.037) for the 12-24 PCI group with diabetes. No significant interactions were found for systolic blood pressure and body weight. Conclusion: Cardiac rehabilitation resulted in significant improvements in the lipid panel, diastolic blood pressure, and questionnaire results, regardless of the number of sessions attended. However, no significant benefits for systolic blood pressure were observed.